Nutrition biomarker assessment and exploration of the role of country foods to improve food security in the Sahtú Region, Canada - Mylene Ratelle; Breanna Phillipps; Kelly Skinner; Yvonne Lamers; Larisse Melo; Brian Laird; Leon Andrew; Jessie Yakeleya; Alyssa Bougie; Kirsten Jensen; Deborah Simmons (International Journal of Circumpolar Health)
Country foods (i.e. wild traditional food) are associated with improved nutrition for northern populations. In response to community concerns, a project was implemented from 2019 to 2021 in the Sahtú region, Northwest Territories, Canada, to: 1) analyse nutrition biomarkers (vitamins A, B1, B2, B6, B12, D, E, folate, P, Na) in blood samples, in order to assess nutritional status and identify nutrient deficiencies, and 2) use a survey to document how access to country foods may improve food security in the community of Tulı́t’a. Findings from the nutritional biomarker assessments (n = 128) indicated that 94% of participants experienced clinical vitamin D deficiency (<20 ng/L of plasma 25-hydroxy-vitamin D3) and 9% had folate deficiency (<8.7 nmol/L total folate). In the previous 12 months, 71% of participants did not always have money to get more food when needed, but 92% of participants said they were not left hungry. Country foods were used to increase the quality or quantity of the diet. Increasing country food consumption, such as fatty fish and large game meat and organs could mitigate the vitamin D and folate deficiencies. Policies should be implemented to improve food security in the North by facilitating access to country food.